PROSPEK PENGEMBANGAN PALA RAKYAT DI PROVINSI LAMPUNG - Fitri Yuni Lestari; Raden Hanung Ismono; Fembriarti Erry Prasmatiwi (Lampung University, 2020)
The aim of this research is to analyze financial feasibility and development prospect of nutmeg farming in Lampung Province. This research was conducted in Gisting Subdistrict, Tanggamus Regency and data were collected in September - October 2017 using a survey method. This reaserch used primary and secondary data. Primary data were used to analyze financial feasibility and obtained by interview technique using questionnaires. The samples size of this research were 30 nutmeg farmers taken using simple random sampling. Secondary data were data in the past seven - nine years to find out the prospect development of nutmeg farming. The data were analyzed using financial feasibility and time series linier with ARIMA model analyses. The results of the study showed that the nutmeg farming was feasible, and development prospect of nutmeg farming based on production and nutmeg seeds export had a good potential for the future.Key words: ARIMA, development, financial, nutmeg, prospect